PENGARUH SIKAP DAN MOTIVASI PETANI TERHADAP ADOPSI PROGRAM KARTU TANI PADA PETANI TANAMAN PADI DI KABUPATEN GROBOGAN - Meliyanawati Meliyanawati; Wulan Sumekar; Tutik Dalmiyatun (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Fertilizer subsidy policy is an effort made by the government to provide facilities to farmers. Based on evaluation of availability and distribution of fertilizers, the government created a farmer card program in hopes of overcoming fertilizer problembs, but the axistence of farmer card program still a pro and a contra among farmers. This research was conducted in Grobogan Regency on 12 February 2019 to 5 march 2019. the purpose of this research was to analyze the attitude, motivations, adoption and the effect of rice farmers attitudes and motivations on adoption of farmer card program. The methods used in this research was survey method. The population used in this research is rice farmers who are members of the outstanding farmers group in Grobogan Regency (Maju farmers group, Margo Husodo farmers group, Karya Mukti farmers group). Research samples was determined randomly with a tota; of 86 respondents obtained from the slovin formula. Data collection is done using interviews and direct observation. Data were analyzed using multiple linear regression test. The result of the research showed that respondents characteristics were dominated by male farmers who were still in productive age who had a long farming experience, but had a relatively low education level. Farmers attitudes, motivations and adoptions of the farmer card program were classified as medium. Attitude and motivation factors affect adoption. Attitude and motivation variables affect the adoption variable 70,4%. Attitude and motivation variables have a very real influence on the adoption variable.